Environmental clearance conditions in impact assessment in India: moving beyond greenwash. Issue 3 (4th May 2022) - Hegde, Mahabaleshwar; Patel, Kirit; Diduck, Alan P.
ABSTRACT: This paper examines the EIA process and its effectiveness in addressing the impacts of a 190 km long national highway project along the Karnataka coast. We analyse the quality and relevance of the environmental clearance conditions established by the Ministry of Environment, Forest, and Climate Change (MoEF&CC) and discusses their potential implications. The findings underline that most of the conditions that pertained to the prevention of pollution, restoration of mangroves, and protection of biodiversity lacked a scientific basis and specific information required for effective implementation. The MoEF&CC also overlooked the social impact of the project and underplayed its own role in ensuring fair compensation to project affected communities for the loss of their land and other livelihoods. The paper concludes by promulgating a long list of irrelevant and ineffective environmental conditions that represent greenwashing because it could misguide affected communities and other stakeholders by creating the impression the state is exercising due diligence in protecting the environment.